Respuesta:
a) 157
b) 36
c) 5
Explicación paso a paso:
a) 100 - (2^10/(2^4)^2) + 4^3 - ([tex]\sqrt[3]{27}[/tex])
= 100 - (2^10/2^8) + 64 - 3
= 100 - (2^2) + 61
= 100 - 4 + 61
= 157
e) [6^11/(6^3)^3]/6^0
= [6^11/(6^9)]/1
= 6^2
= 36
f) [tex]\sqrt{100 - 36}[/tex] + 8(9 - 6) - {[3^2 * (3^7)^3] /3^20}
= [tex]\sqrt{64}[/tex] + 8 * 3 - {[3^2 * (3^21)] / 3^20}
= 8 +24 - {3^23}/ 3^20}
= 32 - {3^3}
= 32 - 27
= 5
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Respuesta:
a) 157
b) 36
c) 5
Explicación paso a paso:
a) 100 - (2^10/(2^4)^2) + 4^3 - ([tex]\sqrt[3]{27}[/tex])
= 100 - (2^10/2^8) + 64 - 3
= 100 - (2^2) + 61
= 100 - 4 + 61
= 157
e) [6^11/(6^3)^3]/6^0
= [6^11/(6^9)]/1
= 6^2
= 36
f) [tex]\sqrt{100 - 36}[/tex] + 8(9 - 6) - {[3^2 * (3^7)^3] /3^20}
= [tex]\sqrt{64}[/tex] + 8 * 3 - {[3^2 * (3^21)] / 3^20}
= 8 +24 - {3^23}/ 3^20}
= 32 - {3^3}
= 32 - 27
= 5